POTENSI AKTIVITAS ANTIOKSIDAN UBI JALAR (Ipomoea batatas L.) UNGU DAN EKSTRAK BUNGA TELANG (Clitoria ternatea L.) DALAM PEMBUATAN PERMEN JELI - Franciscus Sinung Pranata (Department of Food Technology, Universitas Pasundan, Bandung, 2022)
Jelly candy is a confectionery product that can be processed into various variations, both in colors, raw materials and flavors. The addition of food ingredients can be used to increase the nutrients in food products, like jelly candy. The purple sweet potato (Ipomoea batatas L.) is one of the types of tubers that are commonly found in Indonesia. The use of purple sweet potatoes in Indonesia is still every low. The purple sweet potato also has a fairly high fiber content, which is equal to 4,59%. Apart from fiber, purple sweet potato extract also has antioxidant activity. Raw purple sweet potato extract had an IC50 value of 5,00 ppm, steamed purple sweet potato extract had an IC50 value of 47,82 ppm, and boiled purple sweet potato extract had an IC50 value of 86,22 ppm. In addition to purple sweet potatoes, a plant that has good antioxidant activity is blue pea flower (Clitoria ternatea L.), with and IC50 value of 41,36 ppm. The Blue pea flower gets its blue color from the anthocyanin. The blue color of this flower can be used as a natural food coloring, which is much safer than use the synthetic one. Thus, these two ingredients that are high in antioxidants can be used as additional ingredients in the formulation of jelly candy as an addition to nutritional value and natural food coloring.